Biological control of Verticillium wilt of eggplant - Melo, Itamar Soares de; Costa, Cyro Paulino da (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
The antagonistic activity of Trichoderma species against Verticillium wilt of eggplant was evaluated. The studies were undertaken in vitro and in vivo. A clearly defined zone, in which the growth of the pathogen was inhibited, was observed with some isolates of Trichoderma in vitro. The best results of the btocontrol under greenhouse conditions were obtained with Trichoderma hamatum and with the isolate T3 of Trichoderma sp. In a field experiment, T. lignorum and the isolate significantly reduced the disease. The mutants of Trichoderma, obtained by UV irradiation, were not efficient in controlling the disease.